2012
DOI: 10.1590/s0037-86822012000100013
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomine sandflies (Diptera: Psychodidae) in São Vicente Férrer, a sympatric area to cutaneous and visceral leishmaniasis in the state of Pernambuco, Brazil

Abstract: Introduction:In the last decades, a considerable geographic expansion of the leishmaniases in all regions of Brazil has been observed. The present study was carried out to identify the composition of the phlebotomine sandfly fauna and verify the seasonal variation of the main species after environmental changes occurred in São Vicente Férrer Municipality, State of Pernambuco, Brazil. Methods: Captures were carried out during four consecutive nights of each month using Centers for Disease Control and Prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
(40 reference statements)
2
26
1
3
Order By: Relevance
“…However, in this study they were also observed in locations showing effects of human intervention, suggesting some adaptation to the changing environments (5) .…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…However, in this study they were also observed in locations showing effects of human intervention, suggesting some adaptation to the changing environments (5) .…”
Section: Discussionmentioning
confidence: 48%
“…An increase in the abundance and diversity of peridomiciliary sandfl ies has been observed in several areas of Brazil in recent years (5) . It is important to correlate the vector density with favorable environmental aspects for peridomiciliary sandfl ies, such as the presence of vegetation, roots, tree trunks, and organic matter, which are the possible shelters and breeding grounds for the vector (19) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations